2011
DOI: 10.3109/15419061.2011.611920
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine inhibits intercellular coupling in rat cardiomyocytes by ubiquitination of connexin43 gap junctions

Abstract: G α q -stimulation reduces intercellular coupling within 10 min via a decrease in the membrane lipid phosphatidylinositol-4,5-bisphosphate (PIP2), but the mechanism is unknown. Here we show that uncoupling in rat cardiomyocytes after stimulation of α -adrenergic G α q -coupled receptors with norepinephrine is prevented by proteasomal and lysosomal inhibitors, suggesting that internalization and possibly degradation of connexin43 (Cx43) is involved. Uncoupling was accompanied by increased Triton X-100 solubilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…Reduced PIP2 levels inhibit gap junctional coupling in both fibroblasts (van Zeijl et al, 2007) and cardiomyocytes (Hofgaard et al, 2008). Stimulation of cultured cardiomyocytes from neonatal rats with noradrenaline or angiotensin II decrease cell coupling and action potential conduction velocity mediated via a decrease in PIP2 levels (Hofgaard et al, 2008) and in a later study it was demonstrated that noradrenaline induced uncoupling was associated with ubiquitination of Cx43, possibly via Nedd4, and subsequent internalization of Cx43 (Mollerup et al, 2011). …”
Section: Ubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced PIP2 levels inhibit gap junctional coupling in both fibroblasts (van Zeijl et al, 2007) and cardiomyocytes (Hofgaard et al, 2008). Stimulation of cultured cardiomyocytes from neonatal rats with noradrenaline or angiotensin II decrease cell coupling and action potential conduction velocity mediated via a decrease in PIP2 levels (Hofgaard et al, 2008) and in a later study it was demonstrated that noradrenaline induced uncoupling was associated with ubiquitination of Cx43, possibly via Nedd4, and subsequent internalization of Cx43 (Mollerup et al, 2011). …”
Section: Ubiquitinationmentioning
confidence: 99%
“…The majority of the SUMOylated Cx43 was found in the Triton X-100 soluble fraction (Kjenseth et al, 2012), suggesting that Cx43 were not organized in functional gap junctions as gap junction plaques are Triton X-100 insoluble (Musil and Goodenough, 1991; VanSlyke and Musil, 2000). However, gap junctions seem to aquire Triton solubility before internalization (Sirnes et al, 2008) and work in cultured cardiomyocytes show that inhibition of the proteasome and lysosome increase both Triton solubility of Cx43 and intercellular coupling simultaneously, indicating that communicating gap junctions can be part of the soluble fraction (Mollerup et al, 2011). …”
Section: Sumoylationmentioning
confidence: 99%
“…For example, it was previously shown that degradation of cardiac beta/slow myosin heavy chain ( /slow MHC) and MHCIIa occurs by the proteasome, with the involvement of the E3 ligases MuRF1 and MuRF3 [10]. Although Nedd4 was reported to interact with Cx43 in neonatal rat cardiomyocytes [12], its involvement in Cx43 remodeling following heart ischemia has never been assessed. Results presented in Fig.1B show that, both in control and ischemic conditions, Nedd4 is detected at IDs, where it co-localizes with Cx43.…”
Section: Resultsmentioning
confidence: 98%
“…Nedd4 was the first described E3 ubiquitin ligase to be implicated in regulating Cx43 ubiquitination, internalization and autophagic degradation through a mechanism involving recruitment of the endocytotic adaptor Eps15 (epidermal growth factor receptor substrate 15) and the autophagic receptor p62 in cell lines 66, 71 . In neonatal rat cardiomyocytes, Nedd4 has also been reported to interact with Cx43 possibly regulating its ubiquitination and internalization in response to norepinephrine 72 . Further evidence implicating the role of Nedd4 in regulating Cx43 in myocytes was recently reported showing that only under basal conditions, silencing of Nedd4 in the HL-1 mouse atrial cell line led to increased Cx43 protein with a decrease in its ubiquitination levels 64 .…”
Section: Cx43 Internalization In Healthy Cardiomyocytesmentioning
confidence: 99%